Michelangelo's David: Florentine history and civic identity - Paoletti, John T. (Cambridge University Press, 2015)
"This book takes a new look at the interpretations of, and the historical information surrounding, Michelangelo's David. New documentary materials discovered by Rolf Bagemihl add to the early history of the stone block that became the David and provide an identity for the painted terracotta colossus that stood on the cathedral buttresses for which Michelangelo's statue was to be a companion. The David, with its placement at the Palazzo della Signoria, was deeply implicated in the civic history of Florence, where public nakedness played a ritual role in the military and in the political lives of its people. This book, then, places the David not only within the artistic history of Florence and its monuments but also within the popular culture of the period as well"--